A Levelized Cost Analysis for Solar-Energy-Powered Sea Water Desalination in The Emirate of Abu Dhabi - Abdullah Kaya (44754) (2019)
The Emirate of Abu Dhabi heavily relies on seawater desalination for its freshwater needs due to limited available resources. This trend is expected to increase further because of the growing population and economic activity, the rapid decline in limited freshwater reserves, and the aggravating effects of climate change. Seawater desalination in Abu Dhabi is currently done through thermal desalination technologies, such as multi-stage flash (MSF) and multi-effect distillation (MED), coupled with thermal power plants, which is known as co-generation. These thermal desalination methods are together responsible for more than 90% of the desalination capacity in the Emirate. Our analysis indicates that these thermal desalination methods are inefficient regarding energy consumption and harmful to the environment due to CO2 emissions and other dangerous byproducts. The rapid decline in the cost of solar Photovoltaic (PV) systems for energy production and reverse osmosis (RO) technology for desalination makes a combination of these two an ideal option for a sustainable desalination future in the Emirate of Abu Dhabi. A levelized cost of water (LCW) study of a solar PV + RO system indicates that Abu Dhabi is well-positioned to utilize this technological combination for cheap and clean desalination in the coming years. Countries in the Sunbelt region with a limited freshwater capacity similar to Abu Dhabi may also consider the proposed system in this study for sustainable desalination. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su11061691